Factors associated with postoperative recurrence in perforated colorectal cancer: unraveling the high recurrence rate of perforated colorectal cancer - Makoto Takagi; Seongcheol Kim; Masaomi Suzuki; Tetsuyoshi Takayama; Hiroshi Asano (World Journal of Surgical Oncology)
Abstract Background Perforated colorectal cancer exhibits a higher recurrence rate than non-perforated colorectal cancer; however, the reasons for this difference remain unclear. This study identifies factors affecting recurrence in patients with perforated colorectal cancer who underwent R0 surgery. Methods This study included consecutive patients with Stage II or III perforated colorectal cancer who underwent radical surgery at a single center between 2007 and 2020. The comparison group included patients with non-perforated, non-obstructive, non-perforated colorectal cancer who underwent surgery during the same period. Clinicopathological background factors (age, sex, localization, surgical procedure, stoma, T stage, lymphatic invasion, venous invasion, differentiation, extent of lymph node dissection, number of dissected lymph nodes, lymph node metastasis, postoperative complications, and 30-day postoperative death) of perforated and non-perforated colorectal cancers were investigated. Factors influencing recurrence were examined in patients who were followed for more than 3 years after surgery, up to 5 years postoperatively. Results This study included 89 perforated and 323 non-perforated cases. The median patient ages were 74 and 73 years in the perforated and non-perforated groups, respectively. In perforated cases, the proportion of T4 stage tumors was significantly higher (39% vs. 18% in non-perforated cases, with p < 0.001). Additionally, the number of lymph node dissections was significantly lower (10 vs. 17 in non-perforated cases, p < 0.001), and the rate of postoperative complications was higher (46% vs. 7% in the non-perforated cases, p < 0.001). Postoperatively, 55 perforated and 284 non-perforated cases were available for follow-up. Univariate analysis revealed that perforation, T4 stage, lymph node metastases, and postoperative complications were associated with significantly higher recurrence rates. Multivariate analysis identified T4 stage and lymph node metastases as independent risk factors. Conclusions The recurrence rate of perforated colorectal cancer was higher than that of non-perforated cases, primarily due to advanced disease stages, such as T4 or lymph node metastases. Perforation itself may not directly cause recurrence but reflects cancer progression. Further research is needed to clarify the mechanisms linking cancer progression, perforation, and recurrence.